Complex field measurement in a single pixel hybrid correlation holography - Chen Z.; Singh D.; Singh R.K.; Pu J. (My University, 2025)
We propose a new scheme for the recovery of complex-valued objects in a single-pixel hybrid correlation holography. The idea is to generate an intensity correlation hologram from the correlation of intensity fluctuations obtained over two channels, namely an optical channel equipped with a single pixel detector and a digital channel. The scheme has a theoretical basis which is described to reconstruct the objects from a single pixel detector. An experimental arrangement is proposed and as a first step towards realizing/implementing the technique, simulation of the experimental model was carried to image three complex objects. © 2020 The Author(s). Published by IOP Publishing Ltd.